Archaeology : the basics - Gamble, Clive (Milton Park, Abingdon, Oxon : Routledge, 2015)
'Now in an updated third edition, Archaeology : The Basics provides a straightforward and engaging introduction to the world of Archaeology. This book answers key questions about how and why we practice archaeology and examines the theories and themes underpinning the subject. Fully updated, this new edition includes a wide range of examples and new material on key growth areas including: Evolutionary approaches in current archaeology; The archaeology of landscape and place; Interdisciplinary archaeological practice; The impact and value of archaeology; Conflict archaeology and the politics of the past. With 12 new illustrations, additional case studies and a glossary of key archaeological terms, this text is essential reading for all those beginning to study archaeology and anyone who has ever questioned the past'--Provided by publisher.
What is archaeology? -- How many archaeologies are there? -- Basic concepts -- People -- Materials and objects -- Time and space -- Change and stability -- Power and identity.
'Simultaneously published in the USA and Canada'--Title page verso.
Includes bibliographical references (pages 251-275) and index.
Keywords: Archaeology; Archaeology -- Philosophy; Archaeology -- History